«Descubrir» y «descubrirse» en el románico: un ejemplo catalán de patrimonio de la humanidad - Garganté Llanes, Maria (CEM – Cultura, Espaço & Memória, 2021)
The aim of this work is to present a case study on the identification between Romanesque art and national identity in Catalonia, an association that emerged in the framework of the emergence of national movements at the end of the 19th century, but that was recovered a century later when the process for the declaration of the Romanesque churches of the Boí Valley as a world heritage site by UNESCO began. The identification of the Romanesque with a «national art» is reinforced in this case because it is a Romanesque art located in the heart of the Pyrenees, with the strong symbolic value of the mountain as the «cradle» of the Catalan nation. We will analyse the World Heritage process and its effects in the context of a small territory, with a scarce population and dependent to a great extent on the seasonality of tourism.